ESKALASI PARTISANSHIP POLITIK DALAM PEMBENTUKAN POLARISASI PADA MASYARAKAT DIGITAL: (Studi pada Platform Media Sosial TikTok) - Purboyo, Muhammad Guntur; Junaidi, Junaidi; Amriwan, Azis (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2024)
In the 2014 and 2019 election era, the most dominant platform used was Twitter. This identity formation can be seen from the presence of the terms "Cebong" and "Kampret" as a form of division of partisan groups between the two candidate camps. That's all, the transformation of digital activity on social media has changed the way society interacts with politics. The use of platforms such as TikTok is an integral part of the process of forming expressions of partisanship at the 2024 people's festival. This research aims to analyze the concept of partisanship in Indonesian political sociology, with an emphasis on the role of social media, especially TikTok. This research uses a documentation study method which involves collecting and analyzing data from various relevant documents such as academic articles, research reports, news archives, and documented TikTok content. This research uses a conceptual framework involving Weberian theory of partisanship, filter bubble concept, and literature related of political sociology. The results that will be obtained in this research are the transformation pattern of the use of social media on the personal branding of presidential and vice- presidential candidates in the Indonesian political constellation in 2024. Three types of political polarization on social media, namely ideological polarization, affective polarization, and news audience polarization. This polarization occurs when the information barrier is copied by the bubble filter and echo chamber.